From the Theory of the African Origin of Humankind to Modern Social, Legal and Technological Innovations: a Brief Analytical Excursion into Anthroposociogenesis - D. Traore (Journal of Digital Technologies and Law, 2024)
Objective: to trace the evolution of humanity and to identify the role of various social institutions in order to understand the existential role of laws aimed at ensuring the coexistence of society in the context of technological innovations.Methods: the author used general scientific and special methods of cognition, which allowed tracing the dialectical development of humanity, social transformations and technological innovations.Results: looking back at the history of humanity, which originated on the African continent (the theory of African descent), the author notes the most important changes in the human way of life and environment, which led to the need to build organized societies and regulate social behavior with the help of legislative norms. Law is seen as part of the evolutionary process that was to emerge in the course of human evolution. The critical importance of law in overcoming the global challenges and existential questions of humanity’s continued coexistence arising in the course of evolution is emphasized. In this regard, the historical significance of the Kurukan Fuga Charter of the Malian Empire is emphasized as one of the oldest constitutions in the world, recognized internationally as an important source of legal and political norms for modern societies, regulating the structure of state power and social behaviour, although preserved largely in oral form. It is argued that social and technological change often served as the impetus for the development of new laws. Humanity has many times intervened in its own biological evolution with the help of technology; now it is an important moment from the viewpoint of law and ethics when technology may interfere in further human evolution. The greatest concern in this regard is the era of rapid development of artificial intelligence, which makes new demands on a human being.Scientific novelty: the article shows the role of the African continent in the origin and development of humanity and socio-legal institutions in the light of modern transformations and the construction of a new social reality.Practical significance: the conducted research creates prerequisites for further development of the theory of anthroposociogenesis and in-depth conceptual historical and legal study of the role of the African continent in the development of humanity and its social institutions.